2008
DOI: 10.1158/1940-6207.capr-08-0184
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Derivative of the Natural Agent Deguelin for Cancer Chemoprevention and Therapy

Abstract: The natural compound deguelin has promising preventive and therapeutic activity against diverse cancers by directly binding to heat shock protein-90 and thus suppressing its function. Potential side effects of deguelin over a certain dose, however, could be a substantial obstacle to its clinical use. To develop a derivative(s) of deguelin with reduced potential side effects, we synthesized five deguelin analogues and compared them with the parent compound and each other for structural and biochemical features… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…However, the potential neuronal toxicity of deguelin, which most likely occurs through the inhibition of NADH dehydrogenase (Caboni et al, 2004), raises concern for its use in human cancer patients. Hence, we attempted to develop deguelin derivatives as lead compounds for the development of novel Hsp90 inhibitors (Oh et al, 2007;Kim et al, 2008;Chang et al, 2012). In our structure-activity relationship studies, the 2,2-dimethyl-2H-chromene moiety of deguelin seemed to be responsible for occupying the ATP-binding pocket of Hsp90 via hydrophobic interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential neuronal toxicity of deguelin, which most likely occurs through the inhibition of NADH dehydrogenase (Caboni et al, 2004), raises concern for its use in human cancer patients. Hence, we attempted to develop deguelin derivatives as lead compounds for the development of novel Hsp90 inhibitors (Oh et al, 2007;Kim et al, 2008;Chang et al, 2012). In our structure-activity relationship studies, the 2,2-dimethyl-2H-chromene moiety of deguelin seemed to be responsible for occupying the ATP-binding pocket of Hsp90 via hydrophobic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we and others have demonstrated that deguelin exhibits profound antiproliferative effects on human premalignant and malignant bronchial epithelial cells and a variety of cancer cells without cytotoxicity to normal cells (Chun et al, 2003;Murillo et al, 2009;Lee et al, 2010;Thamilselvan et al, 2011;Kang et al, 2012;Mehta et al, 2013a,b;Suh et al, 2013). Furthermore, deguelin has shown in vivo effectiveness in suppressing the growth of xenograft tumors and lung tumor formation in tobacco carcinogentreated A/J mice and in genetically engineered mice with mutant K-Ras (Chun et al, 2003;Lee et al, 2005;Kim et al, 2008;Woo et al, 2009). Structural biology and molecular modeling techniques have revealed that deguelin exhibits antitumor and antiangiogenic activities by targeting heat shock protein 90 (Hsp90), which functions as a molecular chaperone and is required for the stability and proper function of many oncogenic proteins, including hypoxia inducible factor (HIF)-1a; mutated p53, mitogen-activated protein kinase kinase (MEK1/2); cyclin-dependent kinase 4; erbB2; and Akt (Oh et al, 2007(Oh et al, , 2008.…”
Section: Introductionmentioning
confidence: 91%
“…HIF-1· is a new target for the antiangiogenic therapy of gastric cancer. Deguelin has been reported to be an anti-angiogenic agent that targets HIF-1· in lung cancer (31)(32)(33)(34)(35). Earlier studies showed that the PI3K/ Akt/mTOR pathway regulates HIF-1· protein translation through mTOR (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Deguelin has been reported to be an anti-angiogenic drug that targets HIF-1· in lung cancer (31)(32)(33)(34)(35). To determine the effect of deguelin on expression of angiogenic factors in gastric cancer cells, VEGF and HIF-1· expression were investigated by RT-PCR.…”
Section: Effect Of Deguelin On Hypoxia-inducible Factor-1 · (Hif-1·) mentioning
confidence: 99%
“…CaPR published possibly the first study of angiogenesis targeting in genetically engineered mouse lung carcinogenesis (41), assessing sunitinib (thought to primarily affect the vascular endothelial growth factor receptor [VEGFR]), and published a study of CD36 targeting in chemically induced oral carcinogenesis (42). Four other CaPR papers report targeting in the angiogenesis-related phosphoinositide 3-kinase/Akt/mammalian target of rapamycin (mTOR) pathway (43)-AKT inhibition with the natural agent myoinositol in human bronchial dysplasia (44), which built on earlier work by this group and others in targeting mTOR in genetically engineered mouse lungs (45,46); mTOR inhibition for preventing chemically induced mouse oral carcinogenesis (47); and in vitro and animal model targeting in this pathway with analogues of the natural agent deguelin (48,49). As highlighted by these papers and a CaPR perspective article (50), targeting angiogenesis and the microenvironment are an exciting new frontier of cancer chemoprevention.…”
Section: Chemopreventionmentioning
confidence: 99%